Costs of healthcare-associated infections in an Intensive Care Unit - Leal,Michelle Araujo (2021)
ABSTRACT Objectives: to evaluate hospitalization costs of patients with and without Healthcare-Associated Infections an Intensive Care Unit. Methods: a retrospective case-control study. Data collection was retrieved from the medical records of Intensive Care Unit of a medium-sized public hospital in Goiás-Brazil. For each case, two controls were selected. Data on socioeconomic, clinical, and hospital costs were collected. To verify associations between variables, Odds Ratio and linear regression were calculated. Results: a total of 21 patients diagnosed with Healthcare-Associated Infections and 42 controls were evaluated. The hospitalization cost for patients with infection was four times higher than for non-infection patients (p-value<0.001). There was an association between infection and higher mortality (p-value <0.001), longer hospital-stay (p-value =0.021), and higher hospital costs (p-value =0.007). Conclusions: hospitalization costs of diagnosed Healthcare-Associated Infections patients are high compared to those who do not have this diagnosis.